PENGARUH PEMBERIAN JUS WORTEL TERHADAP PENURUNAN NYERI MENSTRUASI PADA REMAJA PUTRI DI WILAYAH POSYANDU PUSKESMAS KARANGPAWITAN KABUPATEN GARUT TAHUN 2025 - Dayana, Gina Margina; Pangestu, Gaidha Khusnul; Rini, Ageng Septa (SINERGI : Jurnal Riset Ilmiah, 2025)
Dysmenorrhea or menstrual pain is one of the most common gynecological problems experienced by adolescent girls worldwide. The incidence of dysmenorrhea in adolescents at the Karangpawitan Health Center in 2023 reached 127 cases. One way to reduce dysmenorrhea is carrots, which are widely known to contain beta-carotene. Beta-carotene functions to neutralize free radicals, as an anti-inflammatory and anti-analgesic. The purpose of this study was to determine the effect of giving carrot juice on reducing menstrual pain in adolescent girls. This study used a quasi-experimental with a pre-test - post-test with control group design. The population in the study were all adolescents registered as members of the adolescent posyandu in the Karangpawitan Health Center area, totaling 72 people. The sample in the study used purposive sampling of 40 adolescent girls who experienced dysmenorrhea pain and were divided into two groups of 15 people in the experimental group and 15 people in the control group. The instrument used was a numeric pain scale observation sheet. Data analysis used the Wilcoxon test. The results of the study showed that in the experimental group there was a decrease in the intensity of menstrual pain from an average of 5.70 to 1 while in the control group from an average of 5.65 to 2.15. The bivariate results showed a p-value of 0.000. So it is concluded that there is an effect of giving carrot juice on reducing menstrual pain in adolescent girls. It is expected to be information and increase knowledge for adolescent girls in overcoming dysmenorrhea and can carry out independent treatment as daily care in overcoming dysmenorrhea by using carrot juice as a safe way to do it